Definiendo “lo mexicano”. Una clave: persistencias del modelo urbano colonial en los “pueblos mágicos” - Méndez, Eloy; Rodríguez, Sylvia (Diálogos Latinoamericanos, 2013)
The Villages Magic Program started in Mexico with the twenty-first century. The set of urban cores in which it spreads, has had intensive growth and in 2012 had implemented in 83 villages from the perspective of local development in the global context. It is based on a novel approach to propose the revaluation of the nation's collective imaginary supposed location in the periphery of regional urban systems.We emphasize the character of these places while its uniqueness is the magic of the Mexican retained. In cases of Alamos and El Fuerte, the program has influenced the valuation of the cultural patrimony of the villages incorporated, but there is evidence that it operates with the appropriate tools as seen since entering the streets of traditional village. In both the place was built with the matrix colonial village-square.